Lineage II of Southeast Asian/American DENV-2 is Associated with a Severe Dengue Outbreak in the Peruvian Amazon - Williams, M. (2014)
During 2010 and 2011, the Loreto region of Peru experienced a dengue outbreak of unprecedented magnitude and severity for the region. This outbreak coincided with the reappearance of dengue virus-2 (DENV-2) in Loreto after almost 8 years. Whole-genome sequence indicated that DENV-2 from the outbreak belonged to lineage II of the southeast Asian/American genotype and was most closely related to viruses circulating in Brazil during 2007 and 2008, whereas DENV-2 previously circulating in Loreto grouped with lineage I (DENV-2 strains circulating in South America since 1990). One amino acid substitution (NS5 A811V) in the 2010 and 2011 isolates resulted from positive selection. However, the 2010 and 2011 DENV-2 did not replicate to higher titers in monocyte-derived dendritic cells and did not infect or disseminate in a higher proportion of Aedes aegypti than DENV-2 isolates previously circulating in Loreto. These results suggest that factors other than enhanced viral replication played a role in the severity of this outbreak.